2021
DOI: 10.3390/antiox10040571
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Expanded Bioaccessibility of Quercetin-3-Rutinoside and Quercetin Aglycone from Buckwheat Biscuits Formulated from Flours Fermented by Lactic Acid Bacteria

Abstract: The expanded bioaccessibility of rutin (Ru) and quercetin (Q) from buckwheat biscuits (BBs) formulated from liquid-state fermented flours by selected lactic acid bacteria (LAB) were determined after gastrointestinal digestion. Fermentation of buckwheat flours caused a LAB-dependent variation in Ru and Q content. BBs baked at 220 °C for 30 min showed lower content of Ru and Q, and no correlation was found between the content of these compounds in fermented flours and BBs. The expanded bioaccessibility of Ru fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…Gratifyingly, probiotic fermentation is an effective and green method for improving the bioactivities and bioaccessibility of PPs ( 52 ). In addition, the in vitro digestion and colonic fermentationmodel also offers a simple, safe, economical, and controllable tool for investigating ways to increase the bioaccessibility of PPs ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…Gratifyingly, probiotic fermentation is an effective and green method for improving the bioactivities and bioaccessibility of PPs ( 52 ). In addition, the in vitro digestion and colonic fermentationmodel also offers a simple, safe, economical, and controllable tool for investigating ways to increase the bioaccessibility of PPs ( 53 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, despite rutin- (quercetin-3-rutinoside) and quercetin-described bioaccessibility in our previous study [ 12 ], seven other flavonoids before and after digestion in vitro were identified in BB F and BB C, including epicatechin, vitexin, orientin, apigenin, kaempferol, and luteolin ( Table 4 and Table 5 , respectively).…”
Section: Resultsmentioning
confidence: 65%
“…Since the beneficial health effects of flavonoids depend on their absorption in the gut [ 28 , 29 ], their bioaccessibility is important to indicate their possible influence on the human organism. Rutin is the main buckwheat flavonoid, whereas quercetin is present in significantly lower concentrations [ 30 ], and our previous investigation showed that fermentation, baking, and in vitro digestion significantly affect their content [ 12 ]. It was found that the expanded bioaccessibility of rutin from BB F was low, and the BI of quercetin was greater than 1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zielińska et al [ 8 ] showed the reduction of parent antioxidants as well as the formation of Maillard reaction products after buckwheat roasting. The behavior of some buckwheat ingredients during the digestive process and their bioaccessibility (D-chiro-inositol or quercetin) have been determined and shown by Zieliński et al [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%